THE EFFECTIVENESS OF MANGOSTEEN PEELS EXTRACT AGAINST THE TOTAL OF T LYMPHOCYTES IN HIV PATIENTS - Maria Dyah Kurniasari; Edi Dharmana; Hussein Gasem (Universitas Airlangga, 2017)
Introduction: The Province of West Java is one of the highest HIV sufferers in Indonesia that has increased accumulatively in 2013 to 2014. This condition was proven that in 2014 West Java ranked 4th among the provinces with the highest HIV sufferers in Indonesia. HIV has main target to infect a cell that contains of receptor, CD4. CD4 examination routinely is very important to decide HIV replication process. Meanwhile, CD4 test in the laboratory is quite expensive and not always available in every health facilities. Mangosteen peels extract contains of xanthones as an antioxidant, which is needed for body as a prooxidant that can inhibit the replication of HIV and the activity was seen from the total number of lymphocyte. Method:  The human experimental research has been done by Randomized Control Group Pretest-Post Test Design. There were 20 patients sample for each group. In group 1, HIV patients with ARV therapy were given mangosteen peels extract and in group 2, they were given placebo capsule. Wilcoxon Smith test and Mann Whitney U test were used to determine the difference between group 1 and group 2. Result: There is no significant difference between lymphocytes (p: 0.102) to HIV patients with ARV in each group examination. Discussion: The ineffectiveness is caused by the phagocytocity and cytoxity of TNF through the increasing of free radicals in HIV patients.